Agrarian student acculturation to the university: the case of secondary agricultural education students - Menefee, Morgan (Kansas State University, 2015)
The transition to college offers students the chance to explore, experiment with, and eventually begin to solidify their identities (Boyd, Hunt, Kandell, & Lucas, 2003), but for students from agricultural backgrounds, leaving home to head to a more urban area for college constitutes a threat to identity (Breakwell, 1986; Cicognani, Menezes, & Nata, 2011; Proshanksy, 1978). Although education research concerning rural students is plentiful (e.g., Antos, 1999; Donehower, Hogg, & Schell, 2012; Durham & Smith, 2006; Lester, 2012), research specific to agrarian students is sparse (e.g., Dees, 2006). The purpose of this qualitative instrumental case study was to explore and describe the experiences of students from agricultural backgrounds as they transitioned to college and how the transition impacted self-perceived identity. In particular, this study inquired into the difficulties and successes faced by study participants, as well as strategies used for coping with the transition from their agrarian homes to their more urban university setting. Four male and four female participants attended a university situated in the Midwest and majored in agricultural education. These university participants were invited to complete two qualitative interviews, submit photographs they felt represented their home and school lives, invite the researcher to observe any facet of their university experience, and submit the most meaningful assignment completed in college. Additionally, three male and two female high school students anticipating the transition to college were interviewed about their perceptions of the upcoming transition. Analysis of research data revealed that participant identities were impacted by the transition to college, their agrarian backgrounds, and their university experiences. Twenty-three distinct codes emerged from the data and were further categorized into six patterns: merging worlds, differences and tensions, “it’s in my blood,” continuing educational legacy/impact, finding self-identity, and can I go home? This study’s results highlighted, first and foremost, the need for universities to keep statistics on rural student enrollment. Additionally, this study emphasized the need for teachers, advisors, and counselors to be mindful of students’ backgrounds and future plans. Finally, this study demonstrated the importance of exposure to more urban areas and educational opportunities for easing the transition to college in students from agricultural backgrounds.
Keywords: Agriculture education; Rural education; Place identity; College transition; Education, Agricultural (0517); Higher Education (0745)